Efek Metoda Aplikasi dan Dosis Pupuk Hayati Penambat N terhadap Serapan N, Pertumbuhan dan Hasil Tanaman Padi pada Tanah Salin - Toto Bustomi; Betty Natalie Fitriatin; Tualar Simarmata (Soilrens, 2020)
Appropriate method and dosage of N-fixing biofertilizer are the keys to success in increasing N uptake, growth and yield of rice plants on saline soils. Research objectives: to obtain the application method and dosage of N-fixing biological fertilizers which gave the best effect on bacterial populations, N content, N uptake, growth (plant height and number of tillers), yield components (number of panicles per clump, number of grains per panicle, percentage of grain. content, and weight of 1000 grains) and rice yields on saline soils. The research was conducted in June-September 2018 at the BPP Cilamaya Wetan Experimental Garden, using a factorial randomized block design with 3 replications. The first factor is the method of applying N-fixing biofertilizers (300, 400, 700 g. ha-1) and the second factor doses of N-fixing fertilizer (500, 1000, 1500 g. ha-1). The results showed that the application of 1500 g.ha-1-fixing biological fertilizer had the best effect on bacterial populations, N levels, N uptake, plant height, number of tillers, number of panicles per clump, number of grains per panicle, percentage of filled grains, and 1000 grain weight, and increased rice yields on saline soil by 29.70%.